Black authorship under the prism of postcolonial criticism (Tempo e Argumento, 2025)
In recent years, the discussion around decoloniality has advanced in the field of This article intended to address the notion of black authorship from the perspective of post-colonial criticism. The concept of the Black Atlantic was mobilized as a theoretical and methodological contribution to argue in favor of black authorship. Furthermore, it is proposed to think of it as a set of complex, dynamic and diverse knowledge and practices that developed between Africa and elsewhere. In this way, black authorship was defended as a transcultural and transnational intellectual transaction
Keywords: authorship; criticism postcolonial; knowledge